Our solar system! : a stellar neighborhood - McAnulty, Stacy (McAnulty, Stacy. Our universe., 2025)
"Yee-haw! Strap in for one wild ride through our very own solar system, guided by space-travelin' buckaroo Comet himself, while you travel around meeting one impressive star, 8 unique planets, a handful of dwarf planets, and a bonanza of moons, asteroids, and comets"--